Domesticated cynomolgus monkey embryonic stem cells allow the generation of neonatal interspecies chimeric pigs. Issue 2 (28th November 2019) - Fu, Rui; Yu, Dawei; Ren, Jilong; Li, Chongyang; Wang, Jing; Feng, Guihai; Wang, Xuepeng; Wan, Haifeng; Li, Tianda; Wang, Libin; Zhang, Ying; Hai, Tang; et al.
Abstract: Blastocyst complementation by pluripotent stem cell (PSC) injection is believed to be the most promising method to generate xenogeneic organs. However, ethical issues prevent the study of human chimeras in the late embryonic stage of development. Primate embryonic stem cells (ESCs), which have similar pluripotency to human ESCs, are a good model for studying interspecies chimerism and organ generation. However, whether primate ESCs can be used in xenogenous grafts remains unclear. In this study, we evaluated the chimeric ability of cynomolgus monkey ( Macaca fascicularis ) ESCs (cmESCs) in pigs, which are excellent hosts because of their many similarities to humans. We report an optimized culture medium that enhanced the anti-apoptotic ability of cmESCs and improved the development of chimeric embryos, in which domesticated cmESCs (D-ESCs) injected into pig blastocysts differentiated into cells of all three germ layers. In addition, we obtained two neonatal interspecies chimeras, in which we observed tissue-specific D-ESC differentiation. Taken together, the results demonstrate the capability of D-ESCs to integrate and differentiate into functional cells in a porcine model, with a chimeric ratio of 0.001–0.0001 in different neonate tissues. We believe this work will facilitate future developments in xenogeneic organogenesis, bringing us one step closer to producing tissue-specific functional cells and organs in a large animal model through interspecies blastocyst complementation.